Internet security awareness and misuse of social networks of university students (2016)
The use of the Internet and social networking sites profitably to seek for information, for communication, social interaction and for learning and research purposes have been globally applauded by the society including the undergraduates. However, some undergraduates are not adequately informed about online safety measures they could adopt to prevent falling victims to online risks and anti- social behaviour. This study therefore attempts to investigate the level of students ’ awareness in security on the Internet and their level of involvement in online negative activities like bullying, fraud, impersonation and theft of information. The study adopted descriptive research design of the survey type. The sample size for the study was 300 undergraduates randomly selected from six departments in faculties of Education, Arts, and Science, University of Ibadan. Questionnaire was used as instrument for data collection. Data collected were analysed using frequency counts, mean scores and Standard deviation. Pearson Product Moment Correlation was used to analyse data gathered on the research hypothesis. Findings of the study revealed that the students have high level of internet security awareness and low level of participation in online negative social activities. Based on the findings of the study, it was recommended that the University management through the University library and departments should ensure that their campaign on ethical use of the internet and social media continue by organizing more trainings, seminars and workshops to sustain the enlightenment of the students on profitable use of the media.